2010
DOI: 10.1172/jci40659
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 and sphingosine-1-phosphate receptor 2 are vital to recovery from anaphylactic shock in mice

Abstract: Sphingosine kinase 1 (SphK1) and SphK2 are ubiquitous enzymes that generate sphingosine-1-phosphate (S1P), a ligand for a family of G protein-coupled receptors (S1PR1-S1PR5) with important functions in the vascular and immune systems. Here we explore the role of these kinases and receptors in recovery from anaphylaxis in mice. We found that Sphk2 -/-mice had a rapid recovery from anaphylaxis. In contrast, Sphk1 -/-mice showed poor recovery from anaphylaxis and delayed histamine clearance. Injection of S1P into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 61 publications
(100 reference statements)
12
122
1
1
Order By: Relevance
“…These distinct signaling properties likely underlie the differential roles of S1P 1 and S1P 2 in the regulation of barrier integrity: S1pr2 deficiency does not affect baseline vascular permeability but prevents enhanced vascular leakage after antigen challenge or injections of PAF and histamine (Figs 1, and Figs E1 and E2). 20 Consistent with this is the previous observation that baseline permeability was not affected by the presence or absence of eNOS. 22,23 Different from S1P 2 , S1P 1 maintains not only constitutive barrier integrity but protects against barrier disruption caused by anaphylaxis and inflammation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These distinct signaling properties likely underlie the differential roles of S1P 1 and S1P 2 in the regulation of barrier integrity: S1pr2 deficiency does not affect baseline vascular permeability but prevents enhanced vascular leakage after antigen challenge or injections of PAF and histamine (Figs 1, and Figs E1 and E2). 20 Consistent with this is the previous observation that baseline permeability was not affected by the presence or absence of eNOS. 22,23 Different from S1P 2 , S1P 1 maintains not only constitutive barrier integrity but protects against barrier disruption caused by anaphylaxis and inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…These results together imply that S1P 2 alleviates acute vascular permeability largely by acting at a site distal to the release of anaphylactic mediators from mast cells; i.e., very likely at the vasculature itself. Our observations are consistent with the studies by Olivera et al, 20,21 which showed that histamine injection-induced hypothermia and hypotension were aggravated in S1pr2 -/-mice, but are not consistent with that by Oskeritzian et al, 19 which showed that S1pr2 deficiency alleviated vascular leakage and hypothermia after antigen challenge, contrasting to our study. The findings by Oskeritzian et al 19 also differ from our observations, in that PAF or histamine injection-induced vascular leakage and hypothermia were not different between Cui 18 S1pr2 -/-and WT mice.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although MAP levels appeared to be lower than in the other tested cohorts, these observations are unlikely to be attributable to the Sphk1 Ϫ/Ϫ genotype. 28 Because autoregulation serves to maintain organ blood flow during fluctuations in perfusion pressure, the observed lack of correlation between CBF and MAP in Sphk1 Ϫ/Ϫ sham and HF mice indicates that autoregulatory mechanisms were functioning under both conditions (Figure 7). Despite intact autoregulation, CBF measures were qualitatively lower than in the other cohorts, suggesting the presence of a specific Sphk1 Ϫ/Ϫ phenotype.…”
Section: Lack Of Sphk1mentioning
confidence: 99%
“…SK1 mediates ischemic postconditioning in mouse hearts (23) and protects against lipopolysaccharide-induced lung injury via downregulation of JNK (8). Mice deficient in the SK1 enzyme had poor recovery from anaphylaxis and delayed histamine clearance, while mice deficient in the SK2 enzyme had rapid recovery from anaphylaxis (44). In contrast, certain models of inflammation such as Crohn's disease show a deleterious effect of SK as mice treated with an SK inhibitor (39) or mice deficient in the SK1 enzyme (51) had reduced inflammation and colon damage.…”
Section: Discussionmentioning
confidence: 99%